Conservative treatment of Charcot artroparthy in a series of spina bifida patients: the experience of one center and review of the literature - EROL, BÜLENT (LIPPINCOTT WILLIAMS & WILKINS, 2007)
The present study was performed to evaluate the use of patellar tendon-bearing ankle foot orthesis for the treatment of Charcot arthropathy in a series of patients with spina bifida. A cohort of 350 spina bifida patients, ages ranging between 12 months and 22 years were evaluated in our clinic between June 1993 and March 2004. Charcot arthropathy was seen in five of these children. Treatment was initiated with nonsteroidal anti-inflammatory drugs, oral bisphosphonates and immobilization. No change was observed in the patients' symptoms after a month of treatment. At this time, a patellar tendon-bearing ankle foot orthesis was prescribed and used for a period of 6 to 24 months. All patients improved within 2 months. At the end of 2 years of follow-up, three patients are still using the brace without any complaints. One patient still has symptoms, although she is wearing her brace, but she has had significant improvement compared with the initiation of therapy. Non-weight-bearing, immobilization and surgery are the known treatment choices in Charcot arthropathy. Little experience exists about this entity and its treatment. Our experience reveals that the patellar tendon-bearing ankle foot orthesis leads to significant improvement in children with Charcot arthropathy without surgery and immobilization.
Keywords: Charcot arthropathy; conservative treatment; patellar tendon-bearing ankle foot orthesis; spine bifida; FOOT; NEUROARTHROPATHY; MANAGEMENT; ARTHRODESIS; DEFORMITIES; ARTHROPATHY; ANKLE